Comparison The Clinical Pregnancy Rate (CPR) And Ongoing Pregnancy Rate (OPR) In Frozen Embryo Transfers (FETs) Following Either FreezeAll Policy To Prevent Ovarian Hyperstimulation Syndrome - Ahmed, Bipashan; ., Angel; S, Sharma (Jour Med Resh and Health Sci, 2021)
Introduction: Patients undergoing in vitro fertilization (IVF) cycles may not receive embryo transfer (ET) at that controlled ovarian stim-ulation (COS) cycle for several reasons. Focusing on the FET cycle, it is uncertain whether there is a difference in the pregnancy outcome between the cycles following either freeze-all policy or failed fresh ET. Whether the ET in that cycle was unsuccessful or ET was not per-formed, frozen embryo transfer (FET) would be performed thereafter if the embryos have been cryopreserved. Objective: To compare the clinical pregnancy rate (CPR) and ongoing pregnancy rate (OPR) in frozen embryo transfers (FETs) following either freeze-all policy to prevent ovarian hyperstimulation syndrome (OHSS; freeze-all group) or excess embryo cryopreservation after fresh embryo transfer (surplus group). Methods: The freeze-all group comprised 44 FET cycles performed in 25 women between January to December-2020. The surplus group comprised 53 FET cycles performed in 47 women during the same period. The cumulative CPR and OPR according to duration of cryopreservation (interval between cryopreservation and FET) was estimated using Kaplan-Meier plots. Cox regression analysis was used for identifying factor to affect to cryopreservation duration in cycles with pregnancy. Results: In day 2–4 transfer cycles, the crude CPR (40% vs. 18.2%) and OPR (20% vs. 4.5%) were similar between the 2 groups. In day 5 transfer, the crude CPR (33.3% vs. 38.7%) and OPR (33.3% vs. 29%) were also similar between the 2 groups. The cumulative CPR (100% vs. 47.5%) and OPR (100% vs. 33.3%) in day 2–4 transfer as well as the cumulative CPR (46.7% vs. 100%) and OPR (46.7% and 74.8%) in day 5 transfer were also similar between the 2 groups. The median duration of cryopreservation was significantly shorter in the freeze-all group than in the surplus group (19.8 vs. 36.9 weeks, P=0.04). Previous history of delivery was the only factor associated with a shorter cryopreservation duration in cycles with pregnancy (hazard ratio, 0.18; 95% confidence interval, 0.05–0.65; P=0.01). Conclusion: Freezing embryos to prevent OHSS and transferring the frozen embryos later may guarantee an acceptable reproductive outcome.